THE RELATIONSHIP OF CORPORATE PERFORMANCE FACTORS TO CORPORATE GOVERNANCE - Soewignyo, Fanny (JBE (Journal of Business and Economics), 2013)
This study is motivated by the important needs for research to inform current corporate governance debates. Focusing on listed Indonesian financial sectors in year 2009, this study aimed to empirically determine the relationship of corporate performance factors to corporate governance.  A corporate governance index based on five aspects of corporate governance was used, and the three different performance measures were considered as independent variables utilized as proxy of corporate performace.  All listed sub-sectors under finance sector in Indonesia Stock Exchange (IDX) were included in this study.  The results reveal that, earnings per share is positive significantly related to corporate governance, asset turnover is negative significantly related to corporate governance, but market to book value is not significantly related to corporate governance.  Moreover, the results indicated that earnings per share is more important than asset turnover in predicting corporate governance